Dietary intake of dioxins in Japan in 2016 with time trends since 1998. Issue 8 (3rd August 2018) - Tsutsumi, Tomoaki; Matsuda, Rieko; Yanagi, Toshihiko; Iizuka, Seiichiro; Isagawa, Satoshi; Takatsuki, Satoshi; Watanabe, Takahiro; Teshima, Reiko; Akiyama, Hiroshi
ABSTRACT: Total diet samples collected from seven regions throughout Japan in 2016 were analysed for polychlorinated dibenzo- p -dioxins, polychlorinated dibenzofurans and dioxin-like polychlorinated biphenyls (DL-PCBs), known collectively as dioxins. This led to estimates of the latest dietary intake of these contaminants for the general Japanese population (≥1 year old). The average daily intake of dioxins for a person weighing 50 kg, calculated at non-detected congener concentrations assumed to be equal to zero, was estimated to be 0.54 pg TEQ (toxic equivalents) kg −1 body weight (bw) day −1 . This value is well below the tolerable daily intake of 4 pg TEQ kg −1 bw day −1 for dioxins in Japan. The average intake was highest from fish and shellfish, followed by meat and eggs. The TEQ contribution of the fish and shellfish group to the total dietary TEQs was significant (89%). The DL-PCBs accounted for about 67% of the dioxin intake. The latest dioxin intake level was compared with previous estimates from total diet study results obtained annually since 1998 to determine the time trends in the dietary intake of dioxins in Japan. Overall, the average dioxin intake appeared to be decreasing gradually during the period of study. The previous average intakes of dioxins ranged from 0.58 to 1.9 pg TEQ kg −1 bw day −1 . The latest average intake was the lowest since 1998 and was about one-third of the average intake in 1998. This decreasing trend in the dietary intake of dioxins was mainly influenced by the decreased dioxin intakes from two food groups, fish and shellfish, and meat and eggs.